Early recovery of cognition and brain plasticity after surgery in children with low-grade frontal lobe tumors - Zheng, Wenjian; Guan, Xueyi; Zhang, Xianchang; Gong, Jian (Frontiers in Pediatrics, 2023)
Background Low-grade frontal lobe tumors (LGFLT) can be cured through total resection, but surgical trauma could impair higher-order cognitive function. We aim to characterize the short-term natural cognitive recovery and brain plasticity in surgically-treated pediatric patients with LGFLT. Methods Ten pediatric patients with LGFLT were enrolled. Their cognitive function was assessed before the surgery (S0), in the first month post-surgery (S1), and 3–6 months post-surgery (S2), using the CNS Vital Signs battery. DTI and rs-fMRI were performed during the same time periods. Changes of cognition and image metrics between S1>S0 and S2>S1 were analyzed. Results The Motor Speed (MotSp) and Reaction Time (RT) scores significantly decreased in S1 and recovered in S2. Rs-fMRI showed decreased functional connectivity (FC) between the bilateral frontal lobes and bilateral caudates, putamina, and pallidi in S1>S0 (voxel threshold p-unc<0.001, cluster threshold p-FDR<0.05). In S2>S1, FC recovery was observed in the neighboring frontal cortex areas (p-unc<0.001, p-FDR<0.05). Among them, the FC in the caudates-right inferior frontal gyri was positively correlated to the RT (p-FDR<0.05). A DTI Tract-based spatial statistics (TBSS) analysis showed decreased fractional anisotropy and axial diffusivity mainly in the corticospinal tracts, cingulum, internal capsule, and external capsule at 0–6 months post-surgery (TFCE-p<0.05). The DTI metrics were not associated with the cognitive data. Conclusion Processing speed impairment after an LGFLT resection can recover naturally within 3–6 months in school-age children. Rs-fMRI is more sensitive to short-term brain plasticity than DTI TBSS analysis. “Map expansion” plasticity in the frontal-basal ganglia circuit may contribute to the recovery.